A likely association of damselflies with the habitat heterogeneity provided by the freshwater swamp lily, Ottelia ovalifolia, in Eyre Peninsula granite rock-holes, with a review of potential threats to this ephemeral habitat. Issue 2 (3rd July 2021) - Hedges, Brock A.; Austin, Andy D.; Conran, John G.; Taylor, Gary S.; Madden, Chris P.; Weinstein, Philip
ABSTRACT: The granite rock-holes (sometimes called gnammas) across northern Eyre Peninsula (EP), South Australia, are a unique but poorly studied ephemeral freshwater habitat containing a complex invertebrate community. Macroinvertebrate predator occurrence is often sporadic, both spatially and temporally. We aimed to determine if environmental conditions might predict predator occurrence in EP rock-holes. A total of 14 rock-holes were sampled across five granite outcrops along the Eyre Highway. Extensive dip-net sampling was undertaken and nymphs of three damselfly species were recorded from the rock-holes: Austrolestes annulosus (Lestidae), Ischnura aurora, and Xanthagrion erythroneurum (both Coenagrionidae), all in a single rock-hole at Pildappa Rock. This sole rock-hole contained a prominent floating-leaved, rooted aquatic macrophyte: the swamp lily, Ottelia ovalifolia (Hydrocharitaceae), which forms a complex, three-dimensional vegetative structure. Damselflies were hypothesised to be associated with the presence of O. ovalifolia, possibly as a result of the plant providing both suitable oviposition sites for the adults and habitat for nymphs throughout the water column, opportunities not afforded by the aquatic vegetation present in shallow rock-holes. Our findings contribute to the limited ecological information regarding EP rock-holes. We also briefly review potential threats to these ecosystems, an understanding of which will be critical to their management and conservation.